Kontribusi Sistem Pembiayaan Pendidikan Dalam Inovasi Manajemen Keuangan Pesantren - Siti Aimah; Muhammad Husain (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
The objectives of this research are: (1) To find out the implementation of the Education Financing System in financial management innovation of the Pondok Pesantren Darussalam Blokagung Tegalsari Banyuwangi Foundation, (2) To determine the factors in financial management innovation of the Darussalam Islamic Boarding School Foundation Blokagung Tegalsari Banyuwangi. This research uses descriptive qualitative research methods.In this study, the researcher himself became the instrument (human instrument) with the support of the interview guide grid. data collection is more emphasized on observation, interviews, and documentation. Data analysis in this study uses three interactive models, namely data reduction, data presentation and decision making. The validity of the data in this study uses triangulation.The results of the research: Implementation of the Education Financing System in Financial Management Innovation Darussalam Islamic Boarding School Blokagung Tegalsari Banyuwangi: The first stage is in the form of planning which includes (1) deliberations on foundation management and financial management, (2) design of education financing system, (3) data collection and the calculation of the financial amount, the second stage is organizing which includes (1) recruitment of the management team in charge of the system, (2) determination of responsibility for the management team, (3) guidance to managers, the third stage is implementation which includes (1) preparing payment system application, (2) making the SIS Darussalam application (3) system socialization and in the last stage there is an evaluation in the evaluation regarding (1) system evaluation meetings, (2) payment recapitulation reports (3) formation of a team for handling arrears. While the Financial Management Innovation Factors of the Darussalam Islamic Boarding School Blokagung Foundation: (1) supporting factors: (a) the establishment of cooperation in the service of the santri education financing system (b) Always monitoring the work productivity of financial managers. (2) Inhibiting factors: (a) the facilities are still not perfect (b) the lack of understanding of technological sophistication.